Assessing relationships between conformity and meta-traits in an Asch-like paradigm - Spee Kosloff; Spencer Irish; Leigh Perreault; Gabrial Anderson; Alexandra Nottbohm (Social Influence, 2017)
The present study investigated associations between personality and conformity. Early work on this subject employed impactful, experimentally realistic procedures to induce conformity, yet lacked valid personality assessment. Conversely, contemporary work used valid personality assessment but measured conformity in low-impact settings. The present study combined the strengths of these research eras by measuring conformity in an Asch-like paradigm and testing associations with two well-validated meta-traits (Stability and Plasticity). Participants evaluated the humorousness of unfunny cartoons, either while alone (n = 103) or while surrounded by confederates who gave high scripted humorousness ratings (n = 102). Meta-traits were measured with the NEO Five Factor Inventory-3. The influence of confederates greatly increased participants’ humorousness ratings, especially among individuals higher in the meta-trait Stability.